Persepsi Siswa di SMPN 3 Martapura Terhadap Pengenalan Olahraga Pickleball - Zainuddin, Muhammad; Kahri, Ma’ruful; Haffyandi, Recky Ahmad (Jurnal Porkes, 2024)
The purpose of the study was to determine student perceptions before and after being given an introduction to socialization. The method of this research is quasi experiment approach quantitative design pretest posttest one group. The treatment carried out is socialization, this method is used to measure the effectiveness of treatment. The sampling technique is random sampling with a sample of SMPN 3 Martapura students, for the number of samples is 87 people, the instrument used is a questionnaire with a perception questionnaire. The data collection technique uses a questionnaire offline or directly which will be able to analyze the total score, mean, and standard deviation on each statement indicator. For data analysis using one sample T Test with the results of Sig. 2 tailed pretest and posttest equal 0.00 smaller than 0.05 in other words there is a difference in the initial test and final test of students' perceptions of pickleball before and after the introduction.